2018
DOI: 10.1111/cea.13135
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization to minor cat allergen components is associated with type‐2 biomarkers in young asthmatics

Abstract: We suggest that measurement of IgE to minor cat allergen components may be useful when investigating asthma morbidity in cat allergic subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…To date, eight cat‐origin allergens have been identified and registered through the World Health Organization/International Union of Immunological Societies (WHO/IUIS) Allergen Nomenclature Sub‐Committee . Fel d 1, a secretoglobin, is the major cat allergen . (Table ) Although monosensitization to Fel d 1 is common, individuals sensitized to the cat allergens Fel d 2 (an albumin allergen) and Fel d 4 (a lipocalin allergen) are usually also sensitized to Fel d 1 .…”
Section: Fel D1 the Major Cat Allergenmentioning
confidence: 99%
See 3 more Smart Citations
“…To date, eight cat‐origin allergens have been identified and registered through the World Health Organization/International Union of Immunological Societies (WHO/IUIS) Allergen Nomenclature Sub‐Committee . Fel d 1, a secretoglobin, is the major cat allergen . (Table ) Although monosensitization to Fel d 1 is common, individuals sensitized to the cat allergens Fel d 2 (an albumin allergen) and Fel d 4 (a lipocalin allergen) are usually also sensitized to Fel d 1 .…”
Section: Fel D1 the Major Cat Allergenmentioning
confidence: 99%
“…2,[10][11][12] Fel d 1, a secretoglobin, is the major cat allergen. 2,[5][6][7][8][9]13 (Table 1) Although monosensitization to Fel d 1 is common, individuals sensitized to the cat allergens Fel d 2 (an albumin allergen) and Fel d 4 (a lipocalin allergen) are usually also sensitized to Fel d 1. 3 Fel d 1 is a sufficiently dominant allergen that IgE sensitization to Fel d 1 is equivalent to cat extract in predicting cat allergy.…”
Section: Fel D1 the Ma Jor C At Allerg Enmentioning
confidence: 99%
See 2 more Smart Citations
“…Novel data on sensitization patterns have emerged from recent studies that have used component-resolved diagnostics to increase knowledge on sensitization profiles and cross-reactivity [28, 49, 54, 55]. Numerous studies have demonstrated that sensitization, especially high pet-specific IgE levels and co-sensitization, are strongly associated with the prevalence, severity and persistence of asthma [5, 26, 49, 54, 5658]. Among pet-sensitive individuals, increased exposure levels can have considerable public health effects.…”
Section: Bedroom Allergen Exposuresmentioning
confidence: 99%